The last queen - Rochette, 1956- (SelfMadeHero, 2024)
"An epic, emotional tale, The Last Queen follows Édouard Roux, a veteran of World War I whose face is left disfigured from fighting in the trenches. Édouard takes refuge in the studio of animal sculptor Jeanne Sauvage, who gives him a new face in the form of a prosthetic mask. The pair embark on an intense romantic relationship. She introduces him to the artistic community of Montmartre, Paris, and Édouard shows her the majestic mountains of his homeland, the Vercors Massif. He tells her the story of the last queen to live in the region, a bear he saw killed as a child. In the heart of the Cirque d'Archiane valley, he reveals to Jeanne an amazing piece of art, seen by few others, which inspires her to create the masterpiece that will make her famous..."--Amazon.